Constitutional Recognition of International Legal Guarantees of Human Rights and Freedoms under Conditions of Armed Conflict - Mandzii , S. (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The article examines the peculiarities of the constitutional consolidation of international legal guarantees of human rights and freedoms under conditions of armed conflict. The role of international human rights standards and the mechanisms of their integration into the national legal system of Ukraine are analyzed. It is established that the system of guarantees of human rights and freedoms has a comprehensive nature and includes interconnected national and international protection mechanisms. Scientific approaches to understanding international legal guarantees of human rights and their significance for ensuring the effective functioning of the state human rights protection system are considered. Particular attention is paid to the constitutional foundations for incorporating international treaties into the system of national legislation, as well as to the right of an individual to apply to international judicial institutions and international organizations after exhausting domestic legal remedies. It is substantiated that the constitutional consolidation of these provisions creates appropriate legal prerequisites for the implementation of international human rights standards and for the fulfillment by the state of its international obligations. The article analyzes the peculiarities of the realization of human rights and freedoms under martial law and determines the permissible limits of their restriction. It is established that, in conditions of armed conflict, the state may temporarily restrict certain rights and freedoms in order to ensure national security and defense; however, such restrictions must comply with the principles of necessity, proportionality, and temporariness. The constitutional provisions of Ukraine regarding rights and freedoms that cannot be restricted even under martial law, as well as certain provisions of foreign constitutions in this area, are examined. It is concluded that the effectiveness of international legal guarantees of human rights and freedoms depends on the proper level of their constitutional consolidation, the effectiveness of national protection mechanisms, and the state’s compliance with international human rights standards. The study employs a combination of general scientific and special legal research methods, including the formal legal, comparative legal, and systematic methods. These methods made it possible to analyze the provisions of the Constitution of Ukraine, international legal instruments, the constitutions of foreign states, and scholarly approaches to the constitutional recognition of international legal guarantees of human rights and freedoms under conditions of armed conflict.